2020
DOI: 10.14744/eej.2020.48658
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of ProTaper Gold, EdgeTaper Platinum, Flex Gold and Pro-T rotary systems

Abstract: Objective: The aim of this study was to evaluate the cyclic fatigue, torsional behavior and bending resistance of EdgeTaper Platinum [ETP (tip 25, taper 0.06)], Flex Gold [FG (tip 25, taper 0.08)], Pro-T [PT (tip 25, taper 0.08)] and ProTaper Gold [PTG (tip 25, taper 0.08)] systems. Methods: Rotary instruments of ETP, PT, FG, and PTG were used (n=30). Cyclic fatigue tests were performed using an artificial stainless-steel canal with a 60o angle and a 5-mm radius of curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 4 publications
1
32
0
Order By: Relevance
“…Comparison between NiTi and stainless steel in previous studies has shown that NiTi instruments have higher central ability and less canal transportation than stainless steel files [2,3] . Despite the advantages, NiTi instruments seem to be vulnerable to separation by cyclic fatigue or torsional stress [4] . The ProTaper Gold (PTG) (Dentsply Maillefer, Ballaigues, Switzerland) rotary system is a common thermally treated rotary instrument with the same features as the ProTaper Universal (Dentsply Maillefer, Ballaigues, Switzerland) but advanced thermal treatment, named gold treatment [5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison between NiTi and stainless steel in previous studies has shown that NiTi instruments have higher central ability and less canal transportation than stainless steel files [2,3] . Despite the advantages, NiTi instruments seem to be vulnerable to separation by cyclic fatigue or torsional stress [4] . The ProTaper Gold (PTG) (Dentsply Maillefer, Ballaigues, Switzerland) rotary system is a common thermally treated rotary instrument with the same features as the ProTaper Universal (Dentsply Maillefer, Ballaigues, Switzerland) but advanced thermal treatment, named gold treatment [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The ProTaper Gold (PTG) (Dentsply Maillefer, Ballaigues, Switzerland) rotary system is a common thermally treated rotary instrument with the same features as the ProTaper Universal (Dentsply Maillefer, Ballaigues, Switzerland) but advanced thermal treatment, named gold treatment [5] . Complex heating-cooling treatment of these files contributes to a visible titanium oxide layer on the instrument surface, with shape memory alloy, higher flexibility, fatigue resistance, cutting efficiency, and canal centering ability [3,4,[6][7][8][9] . The heat-treated AF-wire of FANTA company is an advancement of NiTi files with enhanced mechanical characteristics and efficient flexibility to prevent dislocation in root canals.…”
Section: Introductionmentioning
confidence: 99%
“…The cyclic fatigue apparatus used in this both studies was previous reported by several authors (MARKS DUARTE et al, 2018;ALCALDE et al, 2018;ALCALDE et al, 2020;WEISSHEIMER et al, 2020). Our study utilized the static instead of the dynamics model due to the static method decrease some biases, such as amplitude of axial motions and speed, wich are completely subjective in a clinical situation because their reproduciton is manually controlled (ALCALDE et al, 2018).…”
Section: Discusionmentioning
confidence: 99%
“…In the second study was used the torsional test to evalaute the maxium torsional strength and angular deflection supported by the instruments before separation. The method used was according the ISO Standadr 3630-1 and has been previously reported by several authors (ALCALDE et al, 2017(ALCALDE et al, , 2018(ALCALDE et al, , 2020. The 3 mm of the tip was fastened and rotation in clockwise direction wa set for all instruments.…”
Section: Discusionmentioning
confidence: 99%
See 1 more Smart Citation